Aquisição do onset complexo no desenvolvimento fonológico típico em crianças entre 2;6 e 5;11 de idade, estudantes de uma creche-escola municipal pública de Maceió-AL - Castro, Maraísa Espíndola de (2015)
This study aims at describing and analyzing the phonological acquisition of complex onset in children with typical phonological development with age ranges from 2;6 (2 years 6 months) to 5;11 (5 years 11 months), who are students of a public primary school in Maceió, Alagoas. The complex onset or branching onset is the syllabic constituent which has two elements in the onset position – an obstruent in the first consonant followed by a liquid consonant. The data analysis was based on the Feature Geometry Theory of Clements & Hume (1995), in Clements (2005) and on the Syllable Theory (SELKIRK, 1984). A total of 40 children, enrolled in the 2013 and 2014 academic years, participated in this research. The data were collected through an assessment with the Child Language Test – ABFW (WERTZNER, 2004) and spontaneous speech. Then, a statistical analysis of the data was conducted by analyzing the influence of phonological environments in complex onset production and the phonological processes. It was observed a late acquisition of complex onset, with children aged from 5;0 to 5;11, in both syllable with obstruent + /l/ and obstruent with //. With respect to influencing variables in the production of CCV syllable, significance was noticed only in the relation between tonicity and the target production of complex onset with non-lateral liquid. In relation to the phonological processes prevalence, it was observed that the most frequent phonological process was the simplification for C1V. Comparing the age groups, there was a gradual decrease in the occurrence of phonological processes, until stabilization of the phonological system of children aged from 5;0 to 5; 11. The analyses of phonological processes and favorable environments conducted provide important information about the acquisition of complex onset, helping in lexicon selection to evaluation and treatment in cases of atypical development, and to development and implementation of a more effective therapy.